2000
DOI: 10.1021/cm991123p
|View full text |Cite
|
Sign up to set email alerts
|

Br···Br and Br···H Interactions in Action:  Polymorphism, Hopping, and Twinning in 1,2,4,5-Tetrabromobenzene

Abstract: The nature and importance of nonbonded halogen−halogen and halogen−hydrogen interactions in molecular crystals continues to attract significant attention. Here, we report the manifestation of such interactions in the twinning and polymorphism of 1,2,4,5-tetrabromobenzene. A combination of molecular modeling and experimental studies using DSC, hot stage optical microscopy, and in situ powder X-ray diffraction is used to explore the mechanism of phase transition and understand the basis of twin formation in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
78
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 17 publications
8
78
0
1
Order By: Relevance
“…Another example of an N-phenylformamide which is chiral in the crystalline state is 4-bromo-2,6-difluoro-N-phenylformamide [Cambridge Structural Database (Allen, 2002) refcode SEDGAJ; Ferguson et al, 1998]. It has been reported that the Br atom is frequently involved in such contacts as a result of its nonspherical shape (Lieberman et al, 2000;Lommerse et al, 1996;Beyer et al, 2001). The molecules in the chains are related by translation, with the aryl rings along the chain stacked parallel to each other.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of an N-phenylformamide which is chiral in the crystalline state is 4-bromo-2,6-difluoro-N-phenylformamide [Cambridge Structural Database (Allen, 2002) refcode SEDGAJ; Ferguson et al, 1998]. It has been reported that the Br atom is frequently involved in such contacts as a result of its nonspherical shape (Lieberman et al, 2000;Lommerse et al, 1996;Beyer et al, 2001). The molecules in the chains are related by translation, with the aryl rings along the chain stacked parallel to each other.…”
mentioning
confidence: 99%
“…3). It has been reported that the Br atom is frequently involved in such contacts as a result of its nonspherical shape (Lieberman et al, 2000;Lommerse et al, 1996;Beyer et al, 2001). Atom Br2 of (I) interacts with atom O1 in the molecule at (x + 1 2 , Ày + 3 2 , Àz + 2) head-on and with atom Br1 in the molecule at (Àx + 3 2 , Ày + 1, z À 1 2 ) side-on (O being a nucleophile and Br an electrophile).…”
mentioning
confidence: 99%
“…The meltw as cooled, and the solid material also movedw hile solidifying. [2][3][4][5][6][7][8][9][10][11] In contrastwith form I, crystals of form III did not show motion, as determined by HSM, and thus, this polymorph was determined not to be thermosalienta bove room temperature. Af ew crystals that did not jump melted at ah igher temperature ( Figure 1B).…”
Section: Resultsmentioning
confidence: 90%
“…Since its first observation, [1] the thermosalient effect-visually striking motion of crystals, whereby they are self-actuated and move rapidly owing to sudden release of strain-was and has remained as erendipitously observed phenomenon. [2][3][4][5][6][7][8][9][10][11][12][13] Early reports of this effect, which occursa saresult of am artensitictype structuralp hase transition, were without exceptiona result of carefulo bservation of crystals during measurement of their melting points, by which point some crystalsw eref ound to "jump"u pon heating in ac apillary or on ah ot stage.S ome of the modern sophisticated methods to determine the melting point or to record thermoanalytical curves by differential scanningc alorimetry (DSC) require crystals to be powdered and/or closed in the sample holder of the instrument. As in either case the sample is visually inaccessible, the thermosalient phenomenon mayh ave been overlooked because any changes in the appearance of the sample during heating could not be visually observed.…”
Section: Introductionmentioning
confidence: 99%
“…This strong fluorescence turn-on is accompanied by vigorous blasting and/or jumping of the crystals in am anner that visually resembles the motility of thermosalient and photosalient solids. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Herein we report the reasons behind the dramatic enhancement of the emission of 3 and we explore the detailed mechanism of the related reaction.…”
mentioning
confidence: 98%